Collection and Evaluation of Some Underutilized Leafy Vegetables of Meghalaya - BURAGOHAIN, J.; SINGH, V. B.; DEKA, B. C.; JHA, A. K.; WANSHNONG, K.; ANGAMI, T. (Indian Journal of Hill Farming, 2014)
The state of Meghalaya is blessed with unique flora and is considered to be the home of many leafy vegetables, which remain underutilized. Considering the importance of these crops in the nutrition and livelihood of the local population, twenty five underutilized leafy vegetables were collected from different parts of Meghalaya and were evaluated for physical and chemical parameters. Among them, Passiflora edulis recorded the highest number of leaves. High dry matter content was recorded in Diplazium esculentum, Fagopyrum cymosum, Eryngium foetidum and Piper longum. Centella asiatica, Chenopodium album, Amaranthus viridis were found to be rich in crude protein. Rumex nepalensis was found rich in pigment content.